Biologization of technologies of leguminous plants cultivation - Ovechko, K. (Дніпров. нац. ун-т залізн. трансп. ім. акад. В. Лазаряна, 2019)
Currently, Ukraine's agriculture needs efficient and at the same time inexpensive means to increase yields and improve the quality of cultivated products, that’s why this technology is of high demand.
Keywords: agricultural production; organization of crop rotation; scientifically grounded crop rotation in agricultural production